Renormalized Solutions of Nonlinear Parabolic Equations in Weigthed Variable-Exponent Space (Journal of Partial Differential Equations, 2015)
" This article is devoted to study the existence of renormalized solutions for the nonlinear p(x)-parabolic problemin the Weighted-Variable-Exponent Sobolev spaces, without the sign condition and the coercivity condition."
Keywords: Weighted variable exponent Lebesgue Sobolev space; Young's inequality; renormalized solution; parabolic problems